Chloramphenicol causes fusion of separated nucleoids in Escherichia coli K-12 cells and filaments. - van Helvoort, J M (1996)
Chloramphenicol is frequently used for better visualization of the Escherichia coli nucleoid. Here, we show that chloramphenicol causes not only rounding off of the nucleoid but also fusion of as many as four separated nucleoids. Nucleoid fusion occurred in fast-growing cells and in filaments obtained by dicF antisense RNA induction or in ftsZ84(Ts) and pbpB(Ts) mutants. Thus, treatment with chloramphenicol erroneously suggests that DNA segregation is inhibited.